1997
DOI: 10.1111/j.1600-0633.1997.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predation and intraspecific interactions on habitat use and foraging by brown trout in artificial streams

Abstract: Abstract— We studied habitat use, foraging rates and behavior of 10 cm and 12 cm long brown trout, Salmo trutta, at two densities, 1.5 and 3.0 fish. m−2, in artificial streams that contained either the amphipod, Gammarus pulex, alone or G. pulex together with the piscivore, northern pike, Esox lucius. Gammarus were stocked in and largely restricted to the pools at a density of 128 Gammurus. m−2. pool−1 Large trout (12 cm) used pools more and riffles less when small trout (10 cm) were present than when small tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 37 publications
2
32
1
1
Order By: Relevance
“…Diet variation in fishes is related to prey availability, their accessibility and the risk of predation (Eggers 1982, Greenberg et al 1997. As a result bigger prey that are easier to capture or with high energetic value are consumed more.…”
Section: Discussionmentioning
confidence: 99%
“…Diet variation in fishes is related to prey availability, their accessibility and the risk of predation (Eggers 1982, Greenberg et al 1997. As a result bigger prey that are easier to capture or with high energetic value are consumed more.…”
Section: Discussionmentioning
confidence: 99%
“…In aquaculture, various factors are associated with weight variation of harvested fish. Some of these factors are genetic differences in growth, social behaviour like Hierarchy, improper feeding and lack of regular sorting (Alanärä & Brännäs 1993Greenberg et al 1997;Baras et al 2000;Alanärä & Kiessling 1996;Gélineau et al 1998;Boujard et al 1992;Coves et al 1998). In our experiment, With regard to non-sorting operation during growth-out period, it's suggested that the sorting operation be carried out at less once in a month.…”
Section: Discussionmentioning
confidence: 99%
“…Microhabitat shifts of small conspecifics in the presence of predators to avoid predation is poorly documented, although it is widely reported for interspecific predation (Fraser and Cerri 1982;Greenberg et al 1997;Harvey 1991;Harvey et al 1988;MacKenzie and Greenberg 1998;Power et al 1985;Schlosser 1987Schlosser , 1988. A common pattern observed in stream fishes is for prey to shift to shallower habitats in the presence of fish predators (Greenberg et al 1997;Harvey 1991;Harvey et al 1988;MacKenzie and Greenberg 1998;Power et al 1985;Schlosser 1987Schlosser , 1988.…”
Section: Introductionmentioning
confidence: 97%